Marketing Islamic Education: Products, Users and Organizational Sustainability - Abidin, Zainal; Magrobi, Maulana (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2023)
In an era of increasingly competitive competition, formal educational institutions need to operate professionally and efficiently. Schools that function as non-profit organizations must adapt to changes in an increasingly competitive educational climate. The research is library research, which relies on analysis of literary sources that are relevant to the topic being studied. In educational services, products include reputation, prospects, and various choices, which are the keys to the success of educational institutions. Product and service differentiation strategies that include reliability, responsiveness, confidence, empathy, and tangibility are important in meeting consumer expectations and creating a positive image for the institution. In Islam, academic culture plays an important role in shaping the behavior of educators, although often ideal values ​​are not fully reflected in society's culture. The role of academic leaders is very influential in introducing and influencing the way individuals carry out organizational values ​​in their daily lives. With a good understanding of market needs and the right strategy, educational institutions can achieve success in meeting the expectations and preferences of prospective students.